Social group membership before treatment for substance dependence predicts early identification and engagement with treatment communities. (3rd September 2019) - Haslam, Catherine; Best, David; A. Dingle, Genevieve; Staiger, Petra K.; Savic, Michael; Bathish, Ramez; Mackenzie, Jock; Beckwith, Melinda; Kelly, Ashleigh J.; Lubman, Dan I.
Abstract: Social relationships play a major role in recovery from substance dependence. To date, greater attention has been paid to the role of important individuals in a person's life and their contribution to recovery following treatment. This study is the first to examine both individual and wider group-based social connections in the lead up to residential treatment for substance misuse in a therapeutic community (TC), and their influence both on a person's readiness to engage with the treatment community and with a recovery pathway. Participants were 307 adults interviewed early in treatment about their individual- and group-based social relationships prior to treatment entry, their social identification with the TC, as 'a user' and a person 'in recovery', their current recovery capital and quality of life. Correlational analysis showed that only pre-treatment group-based, and not individual, relationships, were significantly associated with developing social identification with the TC early in treatment. Moreover, results of hierarchical regression analyses indicated that identification with the TC was best predicted by the extent to which people saw themselves as being in recovery. Finally, mediation analysis indicated that TC identification was the mechanism through which social group memberships prior to treatment commencement protected quality of life in the early phases of treatment. These findings highlight the protective role that group memberships play in building early identification with the TC and supporting well-being in a critical period of transitioning to treatment.